Primary politics : everything you need to know about how America nominates its presidential candidates - Kamarck, Elaine Ciulla (Brookings Institution Press, 2023)
"Drawing on meticulous research, interviews with key figures in both parties, and years of experience, this book explores one of the most important questions in American politics-how we narrow the list of presidential candidates every four years"--